PMP Driven Probable Maximum Flood for 4 Dams in Sungai Perak Hydroelectric Scheme - Razali J.; Mohd Sidek L.; Marufuzzaman M.; Rakhecha P.R.; M Radzi M.R.; Hossain M.S.; Zawawi M.H. (Springer, 2023)
Probable Maximum Flood is considered as one of the most applied inflow design floods in the determination of dam structure adequacy in current practices. This study revised the inflow design flood values for Sungai Perak Hydroelectric Scheme using Probable Maximum Flood estimation. Probable Maximum Precipitation is analyzed for the catchment and the most critical rainfall values are used in establishing the maximum flood. The revised inflow design flood values for the (4) four dams are found to be 17 259.2m3/s at Temengor Dam, 5 436m3/s at Bersia Dam, 13 522.6m3/s at Kenering Dam and 13 025m3/s at Chenderoh Dam. The inflow design flood values are higher by 2%30% for all four dams in the scheme and these dams are also found to be inadequate in terms of spillway capacities with the percentage of 5%-11% higher than the designed capacities. Further enhancement needs to be done by the dam owner either with or without structural modifications in order to protect the structure and downstream population at risk. 2020, Springer Nature Singapore Pte Ltd.